Compositional stability of sediment microbial communities during a seagrass meadow decline - Markovski, Marsej; Najdek, Mirjana; Herndl, Gerhard J.; Korlević, Marino (Frontiers in Marine Science, 2022)
The presence of seagrass shapes surface sediments and forms a specific environment for diverse and abundant microbial communities. A severe decline of Cymodocea nodosa, a widespread seagrass species in the Mediterranean Sea, has been documented. To characterise and assess the changes in microbial community composition during the decline of a Cymodocea nodosa meadow, Illumina MiSeq sequencing of the V4 region of the 16S rRNA gene was performed. Samples of surface sediments from two sites, one without any vegetation and one with a declining Cymodocea nodosa meadow, were collected at monthly intervals from July 2017 to October 2018. Microbial communities were stratified by sediment depth and differed between the vegetated and the nonvegetated site. Although the Cymodocea nodosa meadow declined to a point where almost no leaves were present, no clear temporal succession in the community was observed. Taxonomic analysis revealed a dominance of bacterial over archaeal sequences, with most archaeal reads classified as Nanoarchaeota, Thermoplasmatota, Crenarchaeota, and Asgardarchaeota. The bacterial community was mainly composed of Desulfobacterota, Gammaproteobacteria, Bacteroidota, Chloroflexi, Planctomycetota, and Campylobacterota. Our results show that sediment microbial communities are remarkably stable and may resist major disturbances such as seagrass meadow decline.